DNA Barcoding and New Records of Odonates (Insecta: Odonata) from Paraíba State, Brazil - Koroiva, Ricardo; Gomes, Vanessa Gabrielle Nóbrega; Vilela, Diogo Silva [UNESP] (MDPI, 2022)
Odonates (Insecta: Odonata) are important insects in the food chains of freshwater envi-ronments around the world, being used as a model species for areas of behavior and analysis of environmental quality. In Brazil, especially in the Northeastern region, both knowledge about the distribution and molecular information of odonate species found in the two main biomes of the region is still limited. Aiming to improve these issues, here, we carried out an Odonata survey in two locations and built a DNA barcode database for species from the state of Paraíba. In total, 15 first records were reported for this Brazilian state and 142 specimens from 27 genera and 45 species had their ‘Folmer’ cytochrome c oxidase subunit I (COI) fragment evaluated. The database we generated includes data for 70% of the Odonata species found in Paraíba state. For 16 species, this is the first DNA barcode available in public sequence repositories. Our results demonstrate that using the COI in the regional scale can help identify and delimit those evaluated. Eight species (17%) showed a low percentage of differentiation (<2%) compared to other species currently deposited in the GenBank or BOLD System; nevertheless, we present morphological traits that reaffirm our identifications. Barcode data provide new insights into Neotropical diversity and deliver basic information for taxonomic analyses.
Keywords: Brazilian northeast; Damselflies; DNA barcode; Dragonfly